CONSUMERS’ PERCEPTIONS AND ATTITUDES TOWARDS OPTICAL DISCS AND ONLINE PIRACY IN MANADO - Robot, Sara Fransisca Caroline (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Piracy is a bad impact of technology development. It is affecting worldwide included Indonesia. But despite the bad impact the piracy brought, many people choose to involve in piracy activity and ignore the morality of their behavior in order to seek the benefit they can get from piracy. This research is designed to have a clearer image and deeper understanding about the consumers’ perceptions and attitudes towards optical discs and online piracy in Manado specifically among university students from 5 universities (De La Salle University, Nusantara University, Politeknik University, Pembangunan Indonesia University and Sam Ratulangi University). The method used in this research is qualitative research methodology with case study research approach and provided a descriptive insight about the piracy phenomenon. The sample of this research is 14 informants who are university students in Manado and participating in piracy. The findings, the university students do think and know the piracy is illegal and bad but because of the advantages of piracy, like cheaper price, easy access to its product and availability of product the university students prefer pirated product rather than original product and ignore the morality of their behavior and current law. The piracy situation like now may be continues to exist in the future. This research suggests the government and related companies to do several proper actions (manage the law and information, more advance in security and technology also teach and guide the people) to fight piracy. Keywords: consumer perceptions, attitudes, piracy, online